2009
DOI: 10.1090/s0025-5718-09-02301-1
|View full text |Cite
|
Sign up to set email alerts
|

Disk-like tiles and self-affine curves with noncollinear digits

Abstract: Abstract. Let A ∈ M n (Z) be an expanding matrix, D ⊂ Z n a digit set and T = T (A, D) the associated self-affine set. It has been asked by Gröchenig and Haas (1994) that given any expanding matrix A ∈ M 2 (Z), whether there exists a digit set such that T is a connected or disk-like (i.e., homeomorphic to the closed unit disk) tile. With regard to this question, collinear digit sets have been studied in the literature. In this paper, we consider noncollinear digit sets and show the existence of a noncollinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…(II)). Then F (T , D) is a class of tiles studied in the proofs of Propositions 3.7, 3.10 in [16]. Note that A, and hence F (T , A), are obtained from C by changing only one digit of C .…”
Section: Statement Of the Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(II)). Then F (T , D) is a class of tiles studied in the proofs of Propositions 3.7, 3.10 in [16]. Note that A, and hence F (T , A), are obtained from C by changing only one digit of C .…”
Section: Statement Of the Main Resultsmentioning
confidence: 99%
“…For that, we need to prove thatΓ and F are connected. In [16], it has already been shown that Γ is homeomorphic to the closed unit disk for |p| > 0 and it is a rectangle for p = 0 (see (B) of the proof of Proposition 3.4 in [16]). Therefore, our graph-directed IFS in Section 2 satisfies OSC for the connected open setΓ .…”
Section: Remark 44mentioning
confidence: 97%
See 2 more Smart Citations
“…Since the fundamental theory of self-affine tiles was established by Lagarias and Wang ( [13], [14], [15]), there have been considerable interests in the topological structure of self-affine tiles T , including but not limited to the connectedness of T ( [7], [8], [12], [1], [6]), the boundary ∂T ( [2], [19], [22]), or the interior T • of a connected tile T ( [24], [25]). Especially in R 2 , the study on the disk-likeness of T (i.e., the property of being a topological disk) has attracted a lot of attentions ( [5], [16], [23], [11], [6]). For other related works, we refer to [20], [17], [18], [21] and a survey paper [3].…”
Section: Introductionmentioning
confidence: 99%